CLINICAL ASSESSMENT OF CARBON MONOXIDE INHALATION IN FIRE BURN PATIENTS: A STUDY USING PULSE CO-OXIMETRY: A FORENSIC AND HISTOPATHOLOGICAL EVALUATION - Adil Umer Khan; Nasim Irshad; Aisha Rasheed; Shumaila Najeeb; Hafiza Kubra; Nadia Aslam (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Carbon monoxide (CO) poisoning is a common complication in fire burn patients, with potential for severe morbidity and mortality. Accurate detection of carboxyhemoglobin (COHb) levels is essential for clinical management. Pulse CO-oximetry, a non-invasive method, offers an alternative to arterial blood gas (ABG) analysis, but its diagnostic accuracy needs further investigation. Objective: To assess the diagnostic accuracy of pulse CO-oximetry in measuring COHb levels in fire burn patients and to evaluate the histopathological and forensic findings associated with CO poisoning. Study Design & Setting: This was a cross-sectional study conducted over six months at Forensic Medicine Department Liaquat University of Medical And Health Sciences Jamshoro from June 2023 to November 2023. Methodology: We enrolled 90 fire burn patients suspected of CO inhalation. Demographic and clinical data were collected, including age, gender, total body surface area (TBSA) burned, and symptoms like altered mental status, headache, and nausea. Pulse COoximetry was used to measure COHb levels, and blood samples were taken for ABG analysis for validation. Histopathological evaluations of deceased patients’ organs (brain, heart, and lungs) were performed to assess hypoxic injury and ischemic necrosis. Data were analyzed using descriptive statistics, Bland-Altman analysis, chi-square tests, and logistic regression. Results: The study showed a high agreement between pulse CO-oximetry and ABG COHb levels (p<0.001). Histopathological findings revealed significant hypoxic injury and ischemic necrosis in vital organs. Clinical symptoms, such as headache and nausea, were more prevalent in moderate and severe CO poisoning cases. Conclusion: Pulse CO-oximetry is a reliable, non-invasive tool for COHb level measurement in fire burn patients, with strong agreement with ABG results. Histopathological findings reinforce the severity of CO-induced damage.